2008
DOI: 10.1007/s00204-007-0275-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the ifosfamide-induced inhibition of endocytosis in the rat proximal kidney tubule

Abstract: The Fanconi syndrome is a common side effect of the chemotherapeutic agent ifosfamide. Current evidences suggest that chloroacetaldehyde (CAA), one of the main metabolites of ifosfamide activation, contributes to its nephrotoxicity. However, the pathophysiology of CAA-induced Fanconi syndrome is not fully understood. The present work examined the adverse effects of CAA on precision-cut rat renal cortical slices, which allowed studying the toxic effect of CAA on proximal endocytosis. We demonstrated that clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Another suspected pathway in rat proximal tubules is endocytosis inhibition resulting from CAA-induced decrease in ATP levels [117].…”
Section: Ifosfamidementioning
confidence: 99%
“…Another suspected pathway in rat proximal tubules is endocytosis inhibition resulting from CAA-induced decrease in ATP levels [117].…”
Section: Ifosfamidementioning
confidence: 99%
“…7 Several mechanisms for ifosfamide-induced nephrotoxicity have been reported including oxidative stress, depletion of glutathione and inhibition of endocytosis in renal tubular proximal cells. 8 Ifosfamide (IF) is metabolized by hepatic CYP3A4 and 2B6. IF mustard, which is produced by ring hydroxylation pathway, is the pharmacological active metabolite, whereas chloroacetaldehyde, which is produced from chlorethyl side oxidation, is largely believed to be responsible for the nephrotoxic effects of IF.…”
Section: Introductionmentioning
confidence: 99%
“…While both CP and IFO have severe urotoxic side-effects, only ifosfamide is thought to be nephrotoxic, causing tubular damage and resulting in Fanconi syndrome [4][5][6][7]. However, recent studies have demonstrated that CP has nephrotoxicity besides its urotoxicity, which both in turn limit its clinical utility [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%